Numerical analysis of shot peening parameters for fatigue life improvement - Isa M.R.; Zaroog O.S.; Raj P.; Sulaiman S.N.; Shah I.A.; Ismail I.N.; Zahari N.M.; Roslan M.E.; Mohamed H. (American Institute of Physics Inc., 2023)
This study will focus on finding the best parameters for shot peening process on aluminium alloy 2024-T351. The main parameters of shot peening process is shot material, velocity, number of impact and also the angle. Strain and work hardening is allowed on the target material. The simulation method was performed using ABAQUS 6.11. Simulation was run by applying shots on the aluminum alloy with variable velocity, number of impact as well as the angle of impact. Result shows that by increasing the velocity and the number of impact, the compressive residual stress will significantly increase. The result from the angle simulation shows that the highest impact is caused by an angle of 90. 2018 Author(s).